2013
DOI: 10.1108/02635571311312640
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the supply chain social capital

Abstract: PurposeThe aim of this paper is to demonstrate that supply chain social capital has an effect on supply chain integration, which in turn has a significant on firm performance, and then supply chain integration mediates the relationship between supply chain social capital and firm performance.Design/methodology/approachThe authors validated their model and tested the hypotheses using the partial least squares (PLS) structural equation model (SEM).FindingsEmpirical results reveal that the three dimensions of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 61 publications
11
104
4
4
Order By: Relevance
“…It is important to highlight that integration strategies require mutual trust and commitment among supply chain partners (Day, Fawcett, Fawcett, & Magnan, 2013) from the perspective of relational capital. Trust and commitment have become important relational dimensions in previous literature (Fazli, Hooshangi, & Hosseini, 2013;Sambasivan et al, 2011;Yim, & Leem, 2013), and a part from the above dimensions, socialization has shown a significant association with inter-firms relationship (Cousins et al, 2006). Importantly, through empirical finding, Yim, & Leem (2013) has shown a significant relationship between relational capital and supply chain integration.…”
Section: Literature Review and Proposed Research Frameworkmentioning
confidence: 85%
See 2 more Smart Citations
“…It is important to highlight that integration strategies require mutual trust and commitment among supply chain partners (Day, Fawcett, Fawcett, & Magnan, 2013) from the perspective of relational capital. Trust and commitment have become important relational dimensions in previous literature (Fazli, Hooshangi, & Hosseini, 2013;Sambasivan et al, 2011;Yim, & Leem, 2013), and a part from the above dimensions, socialization has shown a significant association with inter-firms relationship (Cousins et al, 2006). Importantly, through empirical finding, Yim, & Leem (2013) has shown a significant relationship between relational capital and supply chain integration.…”
Section: Literature Review and Proposed Research Frameworkmentioning
confidence: 85%
“…Trust and commitment have become important relational dimensions in previous literature (Fazli, Hooshangi, & Hosseini, 2013;Sambasivan et al, 2011;Yim, & Leem, 2013), and a part from the above dimensions, socialization has shown a significant association with inter-firms relationship (Cousins et al, 2006). Importantly, through empirical finding, Yim, & Leem (2013) has shown a significant relationship between relational capital and supply chain integration. In addition, Sambasivan et al (2011) revealed that relational capital was significantly linked with strategic alliance.…”
Section: Literature Review and Proposed Research Frameworkmentioning
confidence: 85%
See 1 more Smart Citation
“…Wei and Ju [32] report on how a partner's social capital can enhance knowledge creation in supply chains. Yim and Leem [33] demonstrate a case where supply chain social capital affecting supply chain integration significantly influences firm performance. Social capital can be an important component of the successful performance of a service supply chain as a source of both physical and informational resources [34].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
“…In accordance with Alfaro and Rábade (2009), the use of traceability information can improve supply chain management. However, a study conducted by Harwood and Humby (2008) highlighted that organisations rarely share information with their supply chain partners, which can have a negative impact supply chain activities like inventory management (Yu, Yan, and Edwin Cheng 2001), resource exchange and collaboration (Yim and Leem 2013).…”
Section: The Traceability Conceptmentioning
confidence: 99%